Extraction and mechanism for the separation of neutral N-compounds from coal tar by ionic liquids. (15th April 2017) - Zhang, Lianzheng; Xu, Dongmei; Gao, Jun; Zhou, Shixue; Zhao, Liwen; Zhang, Zhishan
Graphical abstract: Highlights: The selected ILs shows good extraction performance for neutral N -compounds. The mechanism of the extraction was confirmed to be the formation of hydrogen bond. BmimCl can be easily regenerated and recycled with good performance even 5 times. A green approach was provided for the separation of neutral N -compounds from coal tar. Abstract: Coal tar is one of the valuable chemical materials and energy, from which the nitrogen-containing compounds ( N -compounds), indole, carbazole, pyridine, and quinoline, are mainly separated. In the present work, the imidazolium-based ILs with different anions, 1-butyl-3-methyl-imidazolium chloride (BmimCl), 1-butyl-3-methyl-imidazolium bromide (BmimBr), 1-butyl-3-methyl-imidazolium tetrafluoroborate (BmimBF4 ), 1-butyl-3-methyl-imidazolium disulfate (BmimHSO4 ), and 1-butyl-3-methyl-imidazolium acetate (BmimCH3 COO), were used to separate those N -compounds via extraction. The performances of ILs extraction were evaluated by the extraction efficiency and distribution coefficient. High extraction efficiency and selectivity could be found for the neutral N -compounds, indole and carbazole, by BmimCl than basic N -compounds, pyridine and quinoline. Meanwhile, the optimized conditions were ascertained and the selected ILs could be easily regenerated by water and be sustainable recycled by a back-extraction process. Furthermore, a hydrogen bond was formed between the neutral N -compound and the selected ILs, and the mechanism was confirmed based on the analysis by a molecular simulation. Thus, an approach was provided for the separation of neutral N -compounds from coal tar.